Exploration into the morphology regulation and formation mechanism of spherical nanoscale alumina powders synthesised via the microwave hydrothermal approach - Shuo Wang; Wenjie Fan; Lida Tong; Jinping Yang; Xiwei Qi (Journal of Materials Research and Technology)
The synthesis of ultrafine dispersed spherical alumina is essential for advanced technologies; however, it is hindered by precursor aggregation and uncontrolled growth during fabrication. In this study, ultrafine dispersed spherical alumina precursors were synthesised using a microwave–hydrothermal method with aluminium nitrate (Al(NO3)3·9H2O) and urea (CH4N2O) as raw materials and ammonium sulphate ((NH4)2SO4) as a regulator. Advanced characterisation techniques such as X-ray diffraction, scanning electron microscopy and transmission electron microscopy were employed to analyse the phase composition, morphology and dispersibility of the precursors and α-Al2O3 powder. Results indicated that SO42− inhibited the excessive polymerisation of aluminium polynuclear complexes through coordination, thereby promoting the formation of spherical aluminium hydroxy sulphate hydrate, while rapid water cooling effectively suppressed particle growth and agglomeration. With Al(NO3)3·9H2O to (NH4)2SO4 and Al(NO3)3·9H2O to CH4N2O molar ratios of 0.8 and 1:10, respectively, a hydrothermal temperature of 100 °C, an extended hydrothermal time of 6 h and rapid water cooling, equiaxial alumina precursors with an average particle size of 104 nm were successfully synthesised. The precursors transformed into γ-Al2O3 with an average particle size of 94 nm after calcination at 900 °C and further transformed into spherical α-Al2O3 with good dispersibility and a particle size of 126 nm after calcination at 1200 °C. This research provides guidance for the manufacture of advanced ceramic devices.